Histamine, Neuroinflammation and Neurodevelopment: A Review - Carthy, Elliott; Ellender, Tommas (Frontiers in Neuroscience, 2021)
The biogenic amine, histamine, has been shown to critically modulate inflammatory processes as well as the properties of neurons and synapses in the brain, and is also implicated in the emergence of neurodevelopmental disorders. Indeed, a reduction in the synthesis of this neuromodulator has been associated with the disorders Tourette’s syndrome and obsessive-compulsive disorder, with evidence that this may be through the disruption of the corticostriatal circuitry during development. Furthermore, neuroinflammation has been associated with alterations in brain development, e.g. impacting synaptic plasticity and synaptogenesis, and there are suggestions that histamine deficiency may leave the developing brain more vulnerable to proinflammatory insults. While most studies have focused on neuronal sources of histamine it remains unclear to what extent other (non-neuronal) sources of histamine, e.g. from mast cells and other sources, can impact brain development. The few studies that have started exploring this in vitro, and more limited in vivo, would indicate that non-neuronal released histamine and other preformed mediators can influence microglial-mediated neuroinflammation which can impact brain development. In this Review we will summarize the state of the field with regard to non-neuronal sources of histamine and its impact on both neuroinflammation and brain development in key neural circuits that underpin neurodevelopmental disorders. We will also discuss whether histamine receptor antagonists have been efficacious in the treatment of neurodevelopmental disorders in both preclinical and clinical studies. This could represent an important area of future research as early modulation of histamine from neuronal as well as non-neuronal sources may provide novel therapeutic targets in these disorders.